The Role of Kei Culture in Preventing Religious Conflict Muslim-Christian in Southeast Moluccas - Farneubun, Longginus; Molino, Jeramie Nunag (Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
The situation of Indonesian society on the threshold of the third millennium, feels so anxious. The level of violence in society is quite high. Various kinds of riots, looting and crime was alarming. Among the various riots that reason, including a number of riots and violence that were pitched inter-religious hostility. There is no more reason to superficially say that there is no problem between the religions with the fact that there, especially the riots in the Moluccas and in particular in the Kei-Southeast Moluccas. What is interesting is nevertheless the enormity of the violence, specifically in Kei, conflict can be resolved quickly than in the areas of inter-religious conflict in Indonesia. This is due to the cultural influence is so strong for the people of Kei. This study will examine the importance of inter-religious dialogue with religion and local wisdom culture approach in Kei. The local wisdom of Kei culture as a basic character for preventing social conflict between religions. In analyzing the data, this study uses a qualitative approach and literature study. The results of this study indicate that inter-religious dialogue with the Kei religion and culture approach is a relevant solution for the diverse Kei society.